Rapid micropropagation of cocoyam (Xanthosoma sagittifolium) Schott - Sama, Anne E., author; Hughes, Harrison G., advisor; Johnson, Duane, committee member; Towill, Leigh, committee member (Colorado State University. Libraries, 1993)
Cocoyam (Xanthosoma sagittifolium Schott) was rapidly micropropagated through early subcultures at four and six week intervals and division of the microshoots. Shoot tips of approximately 3-5mm in size were used in the initiation of cultures on a modified B5 basal salt medium for six weeks. Cultures were subsequently micro propagated successfully through several procedures, which included the use of a range of growth regulator levels. Levels of 0.05μM NAA with 5, 10 and 20μM BAP as well as 1, 2 and 4μM TDZ singly or in combinations at the initiation and multiplication stages, as well as on agitated and stationary liquid media. Cultures initiation on solid media or supported on filter paper bridges was unsuccessful. However, solid media were beneficial in shoot multiplication, elongation and rooting stages. The level of 2μM TDZ alone and in combination with 20μM BAP significantly enhanced shoot proliferation, producing an average of 30 microshoots/culture, but repressed root formation. However, root initiation and development was possible in media containing only BAP at all levels tested. Shoot proliferation, elongation and rooting continued on media devoid of plant growth regulators and was independent of the culture vessel employed. A 100% survival of plantlets transferred into the greenhouse was achieved, irrespective of the method of acclimatization and size of the plantlet. Plantlets acclimatized in the humidity tent were less stressed, produced more and shed fewer leaves after two weeks from acclimatization. Differences in level of leaf injury were evident with control plants transferred directly to the open bench, which sustained the highest injury. The high level of survival of plantlets upon transfer to the greenhouse was attributed, in part, to the reduced numbers of stomates found on both abaxial and adaxial leaf surfaces of in vitro cultured plantlets, the high wax content and high rate of rooting.
Covers not scanned.
Keywords: Plant micropropagation; Plant tissue culture; Acclimatization (Plants)